Influence of Nozzle-to-Surface Distance Ratio and Reynolds Number Variation on Hemispherical Tempered Glass Strength and Quench Time - Frans Loekito; Budi Utomo Kukuh Widodo; Djatmiko Ichsani (JMES The International Journal of Mechanical Engineering and Sciences, 2017)
The quenching step in a glass tempering process is a transient heat transfer phenomenon which is governed by several parameters – Reynolds number (Re) and the nozzle diameter-to-surface distance ratio (H/D). In this research, the effect of such parameters on the strength and quench time of hemispherical tempered glass are to be analyzed. The quenching process will use the impinging jets quench method, with an equilateral – staggered nozzle arrangements. The process is performed in an ambient air of 60oC and with a nozzle pitch and diameter of 27 mm and 4 mm respectively. The study applies variations of Reynolds number: 2300, 10000, 20000, 30000, 40000, 50000, 60000, 70000, 80000, and 87000, and H/D: 2, 6, 9, and 12. These variations are used to construct and solve a mathematical model, to obtain temperature distribution contours. The contours are then transformed into stress distribution graphs. From these steps, it is found that the tempered glass strength increases and the quench time decrease along with the increase of Re and the decrease of H/D. It is also found that the allowable range of operation is between Re = 8000 – 25000 for H/D =2 and Re = 8000 – 30000 for H/D = 6, 9, and 12.